The sale of Italian books in Madrid during the reign of Felipe II: Simone Vassalini’s catalogue (1597) - Pedro Rueda Ramìrez (JLIS.it, 2018)
In 1597 in Madrid, the bookseller Simone Vassalini printed what is considered to be the earliest known example of a printed book sale catalogue published in Spain, the Index librorum. The only remaining copy, which once formed part of the private library of the Sardinian jurist Monserrat Rosselló, lists the titles of 875 printed books. Of these, 77.83% are works in Latin and 20.11% are Italian books. The catalogue also lists works in Arabic, Greek and Hebrew. Of all the books, 90.5% were printed in Italy and 69.3% were printed in the Republic of Venice. The main subjects are law, religion, medicine, history, humanities and sciences, although the list also features Italian literary texts and poetry anthologies, which would have been particularly popular in sixteenth-century Spain.